Collapse of the public health system and the emergence of new variants during the second wave of the COVID-19 pandemic in Brazil - Silva, Severino Jefferson Ribeiro da (One Health, 2021)
The worldwide spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the most severe public health crisis since the 1918 Spanish influenza pandemic. After the introduction of public health interventions aimed at reducing the number of COVID-19 cases, many countries across the world obtained success at containing the fast spread of SARS-CoV-2 during the first wave of the pandemic. However, the SARS-CoV-2 has resurged in many countries causing a even more devastating second wave. Brazil is one the most affected countries and currently is facing one of the worst public health crises in its history. Here, we discuss the unprecedented challenges faced by the Brazilian public health system in the midst of the second wave of the COVID-19 pandemic, particularly regarding the collapse of the Brazilian health system and the emergence of new variants of concern (VOCs). Finally, we suggest some insights using a one health approach that will help the country to face and overcome the current COVID-19 crisis.